Peran Budaya Sekolah Dalam Meningkatkan Mutu Pendidikan Dan Menciptakan Lingkungan Belajar Yang Kondusif - Melinda Fitriana Siregar; Achmad Zulfikar Siregar (Jurnal Sosial Politik dan Hukum, 2024)
School culture is a set of values that encompasses behavior, tradition, daily policies, and symbols as implemented by headmaster, teachers and staff, students and society nearby. School culture is a distinctive character and image of the school to the eye of outsiders. A lot can be done to improve education quality by building positive school culture that enables good morale as well as conducive setting which positively impact school’s education quality. In the attempt to develop school culture relevance with current situation should be taken into account. There are positive and negative cultural aspects as well as the neutral one; cultural aspect that is being implemented should be suitable to the realization of school’s vision and mission through the development of a good culture.